Association Between Inflammatory Burden Index and Unfavorable Prognosis After Endovascular Thrombectomy in Acute Ischemic Stroke - Du M; Xu L; Zhang X; Huang X; Cao H; Qiu F; Lan W; Jiang H (Dove Medical Press, 2023)
Mingyang Du,1,* Lili Xu,1,* Xiaohao Zhang,2 Xianjun Huang,3 Hui Cao,1 Feng Qiu,1 Wenya Lan,1 Haibo Jiang1 1Cerebrovascular Disease Center, Nanjing Brain Hospital Affiliated to Nanjing Medical University, Nanjing, Jiangsu Province, 210029, People's Republic of China; 2Department of Neurology, Nanjing First Hospital, Nanjing Medical University, Nanjing, Jiangsu, 210002, People's Republic of China; 3Department of Neurology, Yijishan Hospital, Wannan Medical College, Wuhu, Anhui Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Mingyang Du, Cerebrovascular Disease Center, Nanjing Brain Hospital Affiliated to Nanjing Medical University, No. 264 Guangzhou Road, Nanjing, Jiangsu Province, 210029, People's Republic of China, Tel/Fax +86 25-82296000, Email dmyang0128@126.comBackground: Inflammatory burden index (IBI) is a systemic inflammation indicator that reflects the inflammatory status. We aimed to investigate the prognostic value of IBI after endovascular thrombectomy (EVT) in patients with acute ischemic stroke.Methods: We enrolled patients treated with EVT from a multicenter cohort between June 2020 and December 2021. The IBI was calculated as C-reaction protein × neutrophil / lymphocyte count. The primary outcome was the unfavorable functional outcome (90-day modified Rankin scale score 3- 6). C-statistics and net reclassification indexes were used to assess the predictive accuracy. Multivariable logistic regression models were used to investigate the association between IBI and unfavorable outcome.Results: A total of 295 patients (mean age, 64.0 ± 12.8 years; male, 63.7%) were enrolled in this study. In multivariable models, higher IBI levels were associated with an increased risk of 90-day unfavorable outcome after EVT (per 1-SD: odds ratio, 1.754; 95% confidence interval, 1.241- 2.587; P = 0.002). Restricted cubic spline curve displayed a linear relationship between the IBI level and 90-day unfavorable outcome (P for nonlinearity = 0.410). Besides, IBI was a more accurate biomarker for predicting unfavorable outcomes with the highest predictive accuracy and reclassification indexes.Conclusion: This study demonstrated that higher IBI was associated with an increased risk of 90-day unfavorable outcome in acute ischemic stroke treated with EVT.Keywords: stroke, thrombectomy, inflammatory burden, systemic, prognosis